A 0.13 μm CMOS front-end, for DCS1800/UMTS - Liscidini, A. (IEEE Journal of solid state circuits)
This paper presents a fully integrated CMOS receiver front-end based on a direct conversion architecture for UMTS/802.11b-g and a low-IF architecture at 100 kHz for DCS1800. The two key building blocks are a multiband low-noise amplifier (LNA) that uses positive feedback to improve its gain and a highly linear mixer. The front-end, integrated in a 0.13 μm CMOS process, exhibits a minimum noise figure of 5.2 dB, a programmable gain that can be varied from 13.5 to 28.5 dB, an IIP3 of more than -7.5 dBm and an IIP2 better than 50 dBm. The total current consumption is 20mA from a 1.2V supply.